Utilizing analytics within the realm of e-commerce to manage the procurement - Hnatchuk, Alina; Potančok, Martin; Teplý, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The thesis focuses on examining the utilizing of data analytics in e-commerce specifically for product supply management. The initial section of the qualification work explores the capabilities and methods of data analytics, discussing its applications across various fields and emphasizing its relevance in e-commerce. The second section delves into the supply chain, analysing its management through analytics and investigating tools for data analytics in e-commerce. The third section provides a synthesis of the findings regarding the influence of data analytics on e-commerce. It includes an analysis of the application of Google Analytics and Noibu. The object of study is an e-commerce project, with the research centring on the impact of data analytics from both the supplier and end-user perspectives.
Vedoucí práce: Martin Potančok
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses